(untitled) (Scientific journal of the Fergana State University, 2024)
The article talks about mutually meaningful communities in the poetry of the Fergana Valley and the literature of Azerbaijan during the period of national revival. Prominent representatives of Azerbaijani literature: some lyrical works of Ahmed Javad, Hasan Karabaghi, poets of the Ferghana Valley: Khazini Tora, Nadim Namongoni, Khairat Torakorgani, Anbar Atin, special attention is paid to the general aspects of poetry. The poetry of both peoples emphasizes the freedom of the country, seeing it free and prosperous, the dreams and desires in the hearts of the people, using different names of birds (bulbula) and animals (deer, gazelle) in their works. At the same time, in Azerbaijani and Uzbek poetry of the period of national revival, poetic observations were made on the concepts of national independence, the glorification of human will and its dignity, and the expectations of honesty and justice from the ruling representatives of their time. In this mortal world, the common ideas put forward about the human race living without suffering and harm are of great importance in the works of poets of the two nations. The period analyzed in the article is considered significant in our acquaintance with the language, traditions, national mentality of the two nations represented in the poetry of Azerbaijan and Uzbeks, and especially with the great changes occurring in the poetic thinking of the people.